Cancer patients in cardiology: how to communicate with patients with special psychological needs and manage their cardiac problems in daily clinical practice. Issue 4 (April 2020) - Lestuzzi, Chiara; Annunziata, Maria Antonietta; Nohria, Anju; Muzzatti, Barbara; Bisceglia, Irma; Ewer, Michael S.
Abstract : N/A: Cancer patients are increasingly referred for cardiology evaluations. These patients differ from those routinely seen in cardiology clinics because of their psychological burden and because the therapies and cancer itself can cause cardiac symptoms. A humane approach is critical to managing these patients. Cardiologists may see patients who are newly diagnosed with cancer or are in various phases of treatment; these patients may or may not have preexisting cardiac disease, and may develop cardiotoxicity from chemoimmunotherapy or radiotherapy. Each of these situations presents unique communication challenges for cardiologists. Although some oncology centers provide training in communication skills for their personnel, including cardiologists, this training is not widely available to physicians in general hospitals or private practice. This article examines the psychological aspects of cardio-oncology. It offers practical suggestions on how to best communicate with cancer patients in different phases of oncology care, and discusses when professional psychological help is needed.